On the zoosemiotics of health and disease - Turovski, Aleksei (Sign Systems Studies, 2002)
The main feature of the signs of health in the animal habitus and behaviour can be characterised as the readiness to adequately (for a species) serve the need for impression (in animalistic elements of the Umwelt). The signs of disease, however multifarious and diverse, generally display certain lack of Umwelt-oriented attentiveness, alertness. Attention of deeply afflicted animals is strongly Innenwelt-oriented; and in some species a set of such signs, suggesting sickness or mortal disease is used as a set of traits in the mimicry of dying. The semiotic factors in health-disease relationships are apparently connected with intuition — like responses creating in the semiosphere a structure of Umwelt-Innenwelt polarized tensions, important in ecological and evolutional developments.